IMAGE RESTORATION TECHNIQUES USING MAXWELL BOLTZMANN DISTRIBUTION - Yulianto Agung Rezeki (Politeknik Negeri Media Kreatif, 2022)
Image restoration technology has many functions and roles in various fields. With the image restoration technology, it is easy for human to describe something through the displayed pictures. However, in practice there are many shortcomings, one of which is the amount of noise and the resulting image is not clear. Therefore, the image restoration method is a solution that can be used to solve this problem. With image restoration, the image that have been previously produced can be modified so that the results are clearer. Maxwell Boltzmann distribution plays a very important role in supporting this image restoration method. The applications in Maxwell Boltzmann we will discuss in here are image restoration filters with Simulated Annealing in magnitude image restoration, modelling in adaptive spatial image restoration, and endoscopic image restoration. In conclusion, image technology can be found in various fields and with different technologies.